Cherry leaf roll virus abundant on Betula pubescens in Finland - Jalkanen, Risto; Büttner, Carmen; Bargen, Susanne (Silva Fennica, 2007)
Virus-related symptoms such as vein banding, leaf roll, chlorosis and subsequent necrosis on birch leaves were increasingly recorded throughout Finland since 2002. They are widespread in this country and have also been detected in northern Norway and Sweden. Symptomatic foliage has so far been found on Betula pendula, B. pubescens, B. pubescens subsp. czerepanovii, and B. nana. A Cherry leaf roll virus (CLRV) specific IC-RT-PCR was applied to young leaves, buds and catkins of symptomatic shoots of nineteen pubescent and one silver birch trees grown in the centre of Rovaniemi, Finland. CLRV was found in seventeen B. pubescens trees. This is the first time that B. pubescens has been confirmed to be a host species for CLRV in Finland. Nor has CLRV been recorded earlier in northern Finland.